x*x+(x*x+6)=90

Simple and best practice solution for x*x+(x*x+6)=90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x*x+(x*x+6)=90 equation:



x*x+(x*x+6)=90
We move all terms to the left:
x*x+(x*x+6)-(90)=0
Wy multiply elements
x^2+(x*x+6)-90=0
We get rid of parentheses
x^2+x*x+6-90=0
We add all the numbers together, and all the variables
x^2+x*x-84=0
Wy multiply elements
x^2+x^2-84=0
We add all the numbers together, and all the variables
2x^2-84=0
a = 2; b = 0; c = -84;
Δ = b2-4ac
Δ = 02-4·2·(-84)
Δ = 672
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{672}=\sqrt{16*42}=\sqrt{16}*\sqrt{42}=4\sqrt{42}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-4\sqrt{42}}{2*2}=\frac{0-4\sqrt{42}}{4} =-\frac{4\sqrt{42}}{4} =-\sqrt{42} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+4\sqrt{42}}{2*2}=\frac{0+4\sqrt{42}}{4} =\frac{4\sqrt{42}}{4} =\sqrt{42} $

See similar equations:

| 7x-x=30= | | v+16/3=9 | | (6c-5)+(-6c)=0 | | 5(v+2)=40 | | 65+15x=-35 | | 9.8x+34.93=-10.2x+34.71 | | 13=m/3+10 | | 2y+y=5y+7 | | 600=9m+60 | | 12x^2+5x-42=0 | | x18=4.5 | | 17-+2c=24 | | 6x+20+x+40+4x-5=180 | | 10.5=(2+5)×h÷2 | | x15=2030 | | 2a-3a=-4= | | 19-g=7;g=15 | | 3x^2+60=180 | | 2,685=115m+500 | | 19-g=7;15 | | 30p+25=20p+65 | | D=144t-16t^2 | | (4x)+(2x+20)=180 | | 3x^2+60+2x^2-25=180 | | x•x+4x=5 | | 500m+115=2,685 | | x-7=3-2 | | 25p+30=65p-20 | | t=5(9+t)÷2 | | 500+115m=2,685 | | 17=(17x/3) | | x*4=180 |

Equations solver categories